2007
DOI: 10.1111/j.1439-0264.2006.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Branching Patterns of the Left Main Coronary Artery in the Dog Demonstrated by the Use of Corrosion Casting Technique

Abstract: As many investigators use dogs as experimental models in catheterization-, ligation-, and collateral flow studies, knowledge and awareness of the canine left coronary artery anatomical variation is vital for differentiation between canine and human coronary arterial patterns and canine and human coronary congenital anomalies with or without circulatory importance. The present study was performed to examine and review the various principal subdivisions of the canine left main coronary artery (LMCA) in vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
8
22
0
Order By: Relevance
“…In the studied goats the right coronary artery was single and was found to be less developed than the left coronary artery. Similar observations were made in ruminants (Nickel et al 1981;Barone 1996), reo deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), European bison (Kupczyńska et al 2015) and Angora rabbit (Bahar et al 2007). However, in dog was described the additional right coronary artery (Bezuidenhout 2013) while in chinchilla the right coronary artery was absent Ozdemir et al (2008).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the studied goats the right coronary artery was single and was found to be less developed than the left coronary artery. Similar observations were made in ruminants (Nickel et al 1981;Barone 1996), reo deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), European bison (Kupczyńska et al 2015) and Angora rabbit (Bahar et al 2007). However, in dog was described the additional right coronary artery (Bezuidenhout 2013) while in chinchilla the right coronary artery was absent Ozdemir et al (2008).…”
Section: Discussionsupporting
confidence: 67%
“…There were a stronger paraconal interventricular branch and a weaker circumflex branch. This type of trunk morphology has also been described in ruminants (Nickel et al 1981;Barone 1996), roe deer (Frąckowiak et al 2007), Bactrian camel (Yuan et al 2009), donkey (Ozgel et al 2004), porcupine (Atalar et al 2003), ringed seal (Smodlaka et al 2008), chinchilla (Ozdemir et al 2008), cat (Barszcz et al 2014(Barszcz et al , 2016b and European bison (Kupczyńska et al 2015). Whereas Bahar et al (2007) reported that in the Angora rabbit, the common trunk of the left coronary artery was divided into the paraconal interventricular branch, the circumflex branch and the proximal branch of the left atrium.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In this study population of cats, only one individual lacked the main trunk of the LCA. A similar situation was reported in a single dog, suggesting independent origins of the ramus circumflexus sinister and the ramus interventricularis paraconalis (Noestelthaller et al., ; Barszcz et al., ). However, the absence of LCO and the arising of the LCA (then named as circumpulmonary coronary artery) from the RCA was described in three English bulldogs and a boxer (Buchanan, ).…”
Section: Discussionsupporting
confidence: 59%
“…The septal branch originating from the paraconal interventricular branch in all P. concolor individuals in the present study follows the pattern described in 60 % of the twenty domestic dogs analyzed by Noestelthaller et al (2007); and 62.5 % of the eight C. thous individuals dissected by Souza et al (2015b). The other possibilities describe the septal branch originating in the left coronary artery, in the aorta, or in the circumflex branch (Noestelthaller et al).…”
Section: Discussionsupporting
confidence: 82%